Vitality of Giri Kedaton Site as a Religious Tourism Attraction in Sidomukti Village, Kebomas, Gresik - Akhmad Andi Saputra; Surjono Surjono; Christia Meidiana (Journal of Indonesian Tourism and Development Studies, 2015)
Giri Kedaton site belongs to the legacy of cultural heritage that has numorous historical values, especially the history of the spread of Islam and the government in Gresik since the 14th century. Giri Kedaton Site was a kingdom founded by SunanGiri and served as the Core City II Gresik in 1487 AD. Currently Giri Kedaton transforms to become cultural tourism object in religious or pilgrimage tourism sector. In 2002-2005, the local government conducted preservation and conservation activities at the Giri Kedaton site. The purpose of this study was to identify the characteristics as well asto measure the vitality of Giri Kedaton site, and determine the variables that may affect the vitality of the sites. The identification of the characteristics of the GiriKedaton site is explained by researcher by using qualitative descriptive analysis, while the frequency distribution analysis was employed to assess the vitality, and the variable effect was analyzed by multivariate linear regression. Based on its mode value on an analysis of a frequency distribution obtained value vitality giri kedaton site is low,  from the results of linear regression analysis multivariate obtained the best method that is a enter methode, where model is as follows : Y = - 2.884 + 0,075 X1+ 0,039 X2 + 0,055 X3 + 0,119 X4 + 0,174 X5 + 0,115 X6 +  0,108 X7 + 0,110 X8 + 0,071 X9 + 0,158 X10 + 0,005 X11 + 0,92 X12 + 0,159 X13 + 0,265 X14 + 0,153 X15. Based on the result analysis of the regression (t-test) variable influence significantly is government’s support (0.002), sidewalks (0.005) and housings (0.047). The conclusion of this study showed that the Giri Kedaton site has supporting function as religious tourism but there is still lacks of adequate infrastructures and facilities including parking areas and economic facilities. In addition to the length of visit (1-3 hours) and the frequency of visits (first visit) have a low value which indicates that the Giri Kedaton site has limited tourism attraction; in other words, it has not been recognized by most visitors. For the vitality of Giri Kedaton site is low as the travelers rated the infrastructure aspects not sufficient to support the site as a religious tourism attraction. For the multivariate linear regression model used was the enter model and only three independent variables who is influential significantly to the site that is government’s support (X14), sidewalks (X5), conditions of housing facilities (X10). Keywords : giri kedaton, multivariate linear regression, religious tourism, vitality